Analysis of HbA1c levels and characteristics of Hajj pilgrims participating in South Halmahera Province - Kartini M Ali; Rusny Muhammad; Fatmah M Saleh (Poltekkes Kemenkes Bandung, 2026)
Background: Hajj is a physical and spiritual activity that demands excellent health conditions, especially for pilgrims with chronic disease risks such as diabetes mellitus. HbA1c levels are a key indicator for assessing long-term glycemic control, which is highly relevant in predicting the risk of complications during the pilgrimage. Objective: This study aimed to analyze HbA1c levels and identify its correlation with participant characteristics in pilgrims. Methods: This study used an analytic design with a cross-sectional approach, with a sample size of 185 pilgrims from South Halmahera Province. Data were collected using a questionnaire sheet and HbA1c examination. Data were analyzed using the Spearman Test. Results: The results showed that there was a statistically significant correlation between the variables tested (sig. value <0.05). There was a strong positive correlation with a correlation coefficient (r = 0.82) and a very high significance level (P-value< 0.0012). The r value indicates that the higher the Fasting Blood Sugar level of a worshiper, the higher the HbA1c level, reflecting poor long-term glycemic control. Conclusion: The conclusion in this study is that there is a strong and significant positive correlation between Fasting Blood Sugar levels and HbA1c levels in pilgrims of South Halmahera Province. These findings emphasize the importance of screening and strict glycemic management, both instantaneous and long-term blood sugar levels, as part of the pilgrims' health preparation to minimize health risks during the pilgrimage.